Diagnostic Accuracy of the Alice NightOne Single-Belt Monitor for Obstructive Sleep Apnea and Reliability of Wireless Data Transfer - Peng M; Zhang Y; Zhao R; Li J; Zhang X; Deng L; Zhao L; Zhou B; Wang X; Dong X; Han F (Nature and Science of Sleep)
MaoHuan Peng,1,* YuanYuan Zhang,2,* Rui Zhao,3 Jing Li,1 XueLi Zhang,1 LiHua Deng,4 Long Zhao,1 Bing Zhou,1 XinRu Wang,1 XiaoSong Dong,1 Fang Han1 1Department of Sleep Medicine, Peking University People’s Hospital, Beijing, People’s Republic of China; 2Department of General Practice, Peking University People’s Hospital, Beijing, People’s Republic of China; 3Department of Pulmonary and Critical Care Medicine, Peking University People’s Hospital, Beijing, People’s Republic of China; 4Department of Geriatrics, Peking University People’s Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: XiaoSong Dong, Department of Sleep Medicine, Peking University People’s Hospital, Beijing, 100044, People’s Republic of China, 100044, Email dongxiaosong@pkuph.edu.cnObjective: To validate the performance of a single-belt type 3 portable monitor Alice NightOne for diagnosis of obstructive sleep apnea and its reliability in remote data transmission.Methods: Our study included two parts: in-laboratory Alice NightOne (ANO) monitoring (ANOlab) and home sleep apnea testing (HSAT) using ANO (ANOhome). For ANOlab, the participants underwent polysomnography (PSG) with ANOlab simultaneously. For ANOhome, the participants completed unattended overnight ANOhome out of sleep center and PSG was performed in another night. The ANO recordings were transmitted to cloud database wirelessly in addition to traditional wire transmission. Message digest-5 (MD5) algorithm was utilized to verify the integrity of the cloud data.Results: Ninety-one ANOlab and 170 ANOhome recordings were analyzed. Both the respiratory event index (REI) on ANOlab and that on ANOhome were lower than the corresponding apnea-hypopnea index (AHI) on PSG (24.9 ± 20.5 events/h vs 31.6 ± 25.0 events/h, and 26.7 ± 17.0 events/h vs 35.3 ± 21.2 events/h respectively, P < 0.001). Bland-Altman analysis of REI on ANOlab versus AHI on PSG showed a mean difference (95% confidence interval) of − 6.7 (− 8.4, − 4.9) events/h. For REI on ANOhome versus AHI on PSG, the difference is − 8.0 (− 9.9, − 6.0) events/h. With threshold of REI ≥ 5 events/h for OSA diagnosis, ANOhome had 98.8% sensitivity, 90.0% specificity, 99.4% positive predictive value. The MD5 algorithm verified the identity between uploaded cloud data and original data.Conclusion: With single thoracoabdominal belt, Alice NightOne can help diagnosis of obstructive sleep apnea with good sensitivity and specificity, though it may underestimate AHI. Furthermore, it provides reliable support based on solid data teletransmission and scoring synchronization, which may increase the ability of diagnosis and management of OSA through telemedicine.Keywords: home sleep apnea testing, portable monitor, obstructive sleep apnea, telemedicine